KARAKTERISTIK FISIK EDIBLE FILM WHEY KEJU DENGAN PENAMBAHAN MINYAK ATSIRI SEREH DAPUR (Cymbopogon Citratus): Physical Characteristics of Edible Film from Whey Cheese with Lemongrass (Cymbopogon Citratus) Essential Oil Addition - Maftuh Kafiya; Danar Wicaksono (Universitas Darussalam Gontor, 2022)
Edible film from whey has been studied as a protector from anti-microbial attacks. This study aims to examine the physical characteristics of edible film whey with lemongrass essential oil addition as an antimicrobial, especially fungal attacks. The experiment was designed with a complete randomized design (RAL) with 3 repeats consisting of 4 treatments of lemongrass essential oil concentrations, namely control (P1), 0.1% (P2), 0.5% (P3), and 1% (P4). The results showed that the moisture content of edible film with P1, P2, and P3 treatments differed markedly from P0. Meanwhile, the soluble speed of P3 and P2 treatments significant differed with P1 and P0. The thickness of edible film from whey was increased with the addition of lemongrass essential oil concentration.